Using Restricted Cubic Splines to Study the Trajectory of Systolic Blood Pressure in the Prognosis of Acute Myocardial Infarction - Zheng, Shuai; Zhao, Fengzhi; Yang, Rui; Wu, Wentao; Liu, Hui; Ma, Wen; Xu, Fengshuo; Han, Didi; Lyu, Jun (Frontiers in Cardiovascular Medicine, 2021)
ABSTRACT Background: Acute myocardial infarction(AMI) is still the most serious manifestation of coronary artery disease. Systolic blood pressure(SBP) as the best predictor of blood pressure(BP) for acute myocardial infarction, it is necessary to comprehensively and deeply explore its influence on AMI. Methods: 4277 AMI patients were extracted from the MIMIC database. The X2/student’s t test was used to judge the differences between the groups, And use COX proportional hazard regression to identify factors that affect the prognosis of AMI. The SBP was classified as a low group (SBP<90 mmHg), a normal group (90 mmHg